Active and Passive Motion in Complex pH‐Fields. Issue 10 (4th August 2021) - Möller, Nadir; Seiffert, Sebastian; Palberg, Thomas; Niu, Ran
Abstract: We create pH landscapes of increasing spatial complexity by placing ion exchange resin beads of different types and sizes in a closed cell featuring a negatively charged bottom substrate. We thus extend previous measurements in a chemically homogeneous background to investigations in chemically structured backgrounds, which evolve in time. We determine local pH gradients by photometry and study the resulting solvent flows along the substrate by tracking passive tracer particles. Analytical modelling of the dispersion of chemicals is possible for situations with dominantly diffusive transport. We then release phoretic swimmers in differently shaped pH fields and study their motion for selected examples. Catalytic Janus swimmers assembled in the wake of a mobile pH source form a modular swimmer showing a noise‐dominated trajectory. For standard modular swimmers with passive cargo, we identify well‐defined and reproducible swimming trajectory types at and around single pH sources. These include swimmer deflection and swing‐by maneuvers, swimmer trapping and escape, as well as circular orbits. More complicated paths result from combining the pH fields of multiple pH sources. Finally, we address swimmer‐swimmer interactions resulting from the superposition of their own pH fields. Our findings clearly demonstrate the high potential of chemically structured environments for swimmer steering. They can further be rationalized in a simple heuristic model considering the interplay of phoretic flows on different length and time scales and its influence on swimmer speed, orientation and emerging propulsion direction. In view of the vast range of possible combinations, our study has to remain preliminary. We anticipate, however, that it will aid the general understanding of transport experiments in pH‐driven systems and other types of phoresis and thus also help design novel and useful strategies for directed transport on the micro‐scale. Abstract : Investigations on the influence of pH‐gradient‐induced phoretic flow fields on the trajectory of phoretic swimmers. Using fixed large IEX (ion exchange spheres) and smaller mobile IEX, we achieve a superposition of local and global hydrodynamic flows, resulting in a variety of interesting swimmer motions.